SLEDVA turns 20 ?! - Kourtasheva, Bilyana (Sledva : NBU Journal of Humanities and Arts, 2020)
An introductory text on the 20th anniversary of SLEDVA by the editor-in-chief, Bilyana Kourtasheva: the outcome is 40 issues, more than 4000 pages on university culture hallmarked by the New Bulgarian University; among the contributors are both renowned academics and students; some of the aspiring young authors have become well known names in their fields.